Comparison of two editions of Tokyo guidelines for the management of acute cholangitis. Issue 2 (30th June 2013) - Sun, Gang; Han, Lu; Yang, Yunsheng; Linghu, Enqiang; Li, Wen; Cai, Fengchun; Kong, Jinyan; Wang, Xiangdong; Meng, Jiangyun; Du, Hong; Wang, Hongbin; Huang, Qiyang; et al.
Abstract Background The Tokyo guidelines from 2007 (TG07) and 2013 (TG13) were compared for the management of acute cholangitis (AC). Methods We reviewed patients with clinically‐proven AC by detecting purulent biles during biliary drainage. TG07 and TG13 were compared regarding diagnosis, severity grading and prognostic values. New risk factors for 30‐day mortality were investigated. Results Definite diagnosis for 120 eligible patients was made in 104 (86.7%) and 101 (84.2%) cases by TG07 and TG13, respectively (P = 0.36), higher than 61 (50.8%) by Charcot's triad (P < 0.001). Diagnostic overlap and concordance (κ) are 90.8% (109/120) and 0.63 (P < 0.0001). Patients classified into mild and moderate grades by TG07 and TG13 differed significantly (P = 0.043). Both guidelines could not predict clinical outcomes except the needs for multi ERCP session by TG13. Intrahepatic obstruction (OR = 11.2, 95% CI: 1.55–226.9) and hypoalbuminemia (≤ 25.0 g/l; OR = 17.3, 95% CI: 3.5–313.6) were independent risk factors for 30‐day mortality in multivariate model. Conclusion Two guidelines are reproducible and reliable in AC diagnosis but different in severity grading. TG13 are more practical for immediate severity grading, enabling planning treatment upon admission. Intrahepatic obstruction is a new candidate predictor of 30‐day mortality for further assessment.